Financial Literacy for University Students: Helping You Prepare For Life - Kurnianti, Destria; Khairunnisa, Hera; Handarini, Dwi; Marsofiyati; Anwar, Choirul; Sebayang, Karuniana Dianta A.; Yusuf, Muhammad; Mundhiharno; Yaacob, Mohd Hasimi; Sari, Rini Nurmala; Haneul; Malzara, Vidia Ratu Balqis; Safitri, Gita (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2023)
Without good financial planning, it will not be easy to achieve all of one's financial goals in the future. The purpose of this community service is to teach students how to manage finances so that they can understand personal financial planning and be wise in managing their finances. This activity is aimed at students of the Faculty of Business, Economics, and Accountancy Universiti Malaysia Sabah and students of the Faculty of Economics and Management Universiti Kebangsaan Malaysia. Knowledge of financial planning will be taught by a lecturer and a speaker from Finansialku as a digital financial application to introduce how to use the application for financial planning. The result of this event is that students need to have sufficient and good financial literacy in order to be able to prepare their financial condition for the future.